Leon. Worst friends forever - Nicholas, Jamar (Leon, 2024)
"After saving his classmates from The Monocle, and now that he has access to tons of cool crime-fighting gadgets, Leon is the superhero his school needs. Or at least . . . he thinks he is. Leon's vigil-antics make Mom and Principal Principle angry, but even worse, they cause a conflict with his best friend, Carlos, who starts to draw mean comics about Leon. Meanwhile, Leon struggles to keep his mom's superhero identity a secret."--Amazon.com.